2017
DOI: 10.4143/crt.2016.190
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer Effects of a Novel Quinoline Derivative 83b1 on Human Esophageal Squamous Cell Carcinoma through Down-Regulation of COX-2 mRNA and PGE<sub>2</sub>

Abstract: Purpose83b1 is a novel quinoline derivative that has been shown to inhibit cancer growth in human esophageal squamous cell carcinoma (ESCC). This study was conducted to comprehensively evaluate the cytotoxic effects of 83b1 on a series of ESCC cell lines and investigate the mechanisms by which 83b1 suppresses cancer growth based on molecular docking analysis.Materials and MethodsA series of ESCC and nontumor immortalized cell lines were exposed to 83b1 and cisplatin (CDDP) in a dose-dependent manner, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…To describe the relative changes of gene expression level of the target gene compared with the reference gene, the comparative ΔΔCt method was applied for relative quantification in qPCR analysis as we previously reported and it is based on the critical cycle number (Ct) generated by qPCR analysis [ 37 ]. Statistical significance of the differences among groups in MTS proliferation assays and qPCR analysisdata was compared by two-tailed t test or one-way analysis of variance (ANOVA) using GraphPad Prism 5 (Version 5.04; GraphPad Software, La Jolla, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To describe the relative changes of gene expression level of the target gene compared with the reference gene, the comparative ΔΔCt method was applied for relative quantification in qPCR analysis as we previously reported and it is based on the critical cycle number (Ct) generated by qPCR analysis [ 37 ]. Statistical significance of the differences among groups in MTS proliferation assays and qPCR analysisdata was compared by two-tailed t test or one-way analysis of variance (ANOVA) using GraphPad Prism 5 (Version 5.04; GraphPad Software, La Jolla, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Our results demonstrated that the 2-chloro-quinoline ring system had an antiproliferative activity more prominent than others substitutes. Pun et al evaluated an novel quinoline effect in proliferation of esophageal cancer model in vivo, they showed that this compound reduced the tumor size in nude mice xenograft [32]. Mphahlele et al synthesized new thienoquinolines, which showed cytotoxic effects against human breast adenocarcinoma cell line (MCF-7cells) with IC 50 between 0.014 and 1.84 mg/ml [33].…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of synthesized compounds was evaluated against three cancer cell lines, namely Hep3B, SLMT-1, and MCF-7, by standard MTS assay as we reported before [ 53 ]. Cells were seeded in 96 well microtiter plates with a cell density of 5000 for 24 h for anticancer activity screening.…”
Section: Methodsmentioning
confidence: 99%